2013
DOI: 10.1016/j.jpeds.2013.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP2C19 Polymorphisms and Lansoprazole-Associated Respiratory Adverse Effects in Children

Abstract: Lansoprazole-associated upper respiratory infections and ST in children are related in part to CYP2C19 haplotype. Our data suggest that lansoprazole-associated adverse events in children may be mitigated by adjusting the conventional dose in PMs. Additional studies are required to replicate our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 38 publications
4
53
0
3
Order By: Relevance
“…However, two small studies point to the possibility of such a link. Lima et al evaluated the association between CYP2C19 genotype and respiratory adverse events including upper respiratory tract infections and sore throats, using data from a clinical trial of pediatric patients who were treated with lansoprazole [97]. Results of this study showed that the average plasma concentrations in IM/PM (defined as having ≥ one * 2, *3, *8 , or * 9 alleles; N = 45) were higher than NM (without no function alleles, N = 91) (207 ± 179 ng/mL vs 132 ± 141 ng/mL ( p  = 0.04)).…”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, two small studies point to the possibility of such a link. Lima et al evaluated the association between CYP2C19 genotype and respiratory adverse events including upper respiratory tract infections and sore throats, using data from a clinical trial of pediatric patients who were treated with lansoprazole [97]. Results of this study showed that the average plasma concentrations in IM/PM (defined as having ≥ one * 2, *3, *8 , or * 9 alleles; N = 45) were higher than NM (without no function alleles, N = 91) (207 ± 179 ng/mL vs 132 ± 141 ng/mL ( p  = 0.04)).…”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 99%
“…At 6 months, IM/PM phenotype was associated with worsened asthma as compared to NM phenotype (+0.16 vs. −0.13; p  =  0.02) and placebo (+0.16 vs. −0.23; p  < 0.01) at 6 months. The authors proposed that the worsening asthma control in IM/PM at 6 months may be due to upper respiratory tract infections, which was previously documented to be higher [97] within the same cohort with IM/PM phenotype .…”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 99%
“…Mean plasma concentrations were significantly higher in poor versus (n=23, 207±179 ng/mL) extensive (n=33, 132±141 ng/mL) metabolizers (P=0.04). If these findings are replicated in an independent sample, the results may be clinically meaningful as a dosage adjustment may be performed to mitigate the occurrence of these side effects in patients classified as poor metabolizers [75].…”
Section: Pulmonary and Allergy Asthmamentioning
confidence: 87%
“…In a genetic substudy, 279 of the 306 aforementioned participants provided DNA for analysis [75]. The frequency of adverse events with lansoprazole was evaluated in children with single-nucleotide polymorphisms (SNPs) in CYP2C19 as this gene may affect lansoprazole clearance and exposure.…”
Section: Pulmonary and Allergy Asthmamentioning
confidence: 99%
“…The study was designed so that participants had at least 2 weeks between the test protocols to allow for complete recovery, but not more than a month, to reduce chances of participants showing a change in respiratory tests' outcomes unrelated to the experimental design, and in accordance with the American Thoracic Society guidelines (2).…”
Section: Fev 1 Can Be Associated With Reduced Values After Vigorous Ementioning
confidence: 99%